Well-being, preference formation and the danger of paternalism - Mozaffar Qizilbash (Max Planck Institute of Economics, 2009)
Informed or rational desire, capability and prudential value list views of well-being - must accommodate human limitations, as well as address issues about adaptation and paternalism. They sometimes address adaptation by toughening the requirement(s) on those desires, satisfaction of which constitutes well-being. That exacerbates a concern that these accounts if adopted will encourage policies which override actual desires and enforce paternalistic restrictions. Sunstein, like Sen, invokes democratic deliberation to address the adaptation problem, and advocates autonomy promoting paternalistic restrictions. Sunstein and Thaler's 'libertarian paternalism' extends this flavour of argument to cover examples of irrationality from behavioural economics. Their variation of the informed desire account involves highly idealized preferences which cannot, in practical terms, guide a paternalistic social planner, but lead to a potentially large range of cases where paternalistic intervention might, in principle, be justified. I argue that the liberal paternalist policy agenda should as currently conceived be resisted.
Keywords: 330